Monitoring of clinical signs in goats with transmissible spongiform encephalopathies - Konold, Timm (BioMed Central, 2010)
BACKGROUND: As there is limited information about the clinical signs of BSE and scrapie in goats, studies were conducted to describe the clinical progression of scrapie and BSE in goats and to evaluate a short clinical protocol for its use in detecting scrapie-affected goats in two herds with previously confirmed scrapie cases. Clinical assessments were carried out in five goats intracerebrally infected with the BSE agent as well as five reported scrapie suspects and 346 goats subject to cull from the two herds, 24 of which were retained for further monitoring. The brain and selected lymphoid tissue were examined by postmortem tests for disease confirmation. RESULTS: The sensitivity and specificity of the short clinical protocol in detecting a scrapie case in the scrapie-affected herds was 3.9% and 99.6%, respectively, based on the presence of tremor, positive scratch test, extensive hair loss, ataxia and absent menace response. All BSE- and scrapie-affected goats displayed abnormalities in sensation (over-reactivity to external stimuli, startle responses, pruritus, absent menace response) and movement (ataxia, tremor, postural deficits) at an advanced clinical stage but the first detectable sign associated with scrapie or BSE could vary between animals. Signs of pruritus were not always present despite similar prion protein genotypes. Clinical signs of scrapie were also displayed by two scrapie cases that presented with detectable disease-associated prion protein only in lymphoid tissues. CONCLUSIONS: BSE and scrapie may present as pruritic and non-pruritic forms in goats. Signs assessed for the clinical diagnosis of scrapie or BSE in goats should include postural and gait abnormalities, pruritus and visual impairment. However, many scrapie cases will be missed if detection is solely based on the display of clinical signs. PrP(d )accumulation in the brain appeared to be related to the severity of clinical disease but not to the display of individual neurological signs.